State sovereignty and sovereign rights: EU and national sovereignty - Natalia A. Blokhina, Ivan V. Yakoviyk, Sergey S. Shestopal, Pavel P. Baranov, (Opción, 2019)
In this paper, the policy of the EU significantly influencing the content and direction of economic, political, administrative and legal reforms implemented in the candidate countries and neighboring states, as well as foreign policy activities have been analyzed. As a result, a supranational organization of power is able to exert a significant influence on the sovereignty of these categories of states. As a conclusion, the impact on the sovereignty of the state is exercised through the direct authorization of this by the country itself, taking into account national interests, despite the EU’s political aspirations.